The effectiveness of stratified mixed-use development's maintenance management / Nur A’dilah Md Sukri - Md Sukri, Nur A’dilah (Faculty of Architecture, Planning and Surveying, 2015)
The development of the stratified mixed used development is increasing over decade. The overview about the maintenance practice in the stratified mixed use development is included in this paper. The aim of the study to establish factor that can enhance the current practice of stratified mixed-use development’s maintenance. The study is conducted as it answers all the objectives stated. The first objective is to identify the maintenance current practice in the stratified mixed use development. The second objective is to examine the factor affecting current practice stratified mixed-use development’s maintenance. The last objective is to evaluate the end user’s satisfaction with the current practice of stratified mixed-use development’s maintenance. The case study is focused on the area that implemented the mixed use development that is more in urban area. The selected case study is in commercial Center Section 7, Shah Alam and Shop House Jalan Pandan Indah, Ampang. The questionnaire about the satisfaction over the maintenance work conducted is distributed to be evaluated and the end user satisfaction is analyzed. A recommendation to the maintenance management about how to improve the maintenance performance is also given.